Analysis of Non-Performing Financing at Indonesian Islamic Banks - Dwi Anggraini; Nurlela Nurlela; Yus Epi (Sean Institute, 2026)
Non-Performing Financing (NPF) is a key indicator used to measure the level of non-performing financing in Islamic banking. A high NPF ratio indicates an increasing level of financing risk that can affect a bank’s financial performance and stability. This study aims to analyze the level of Non-Performing Financing (NPF), identify constraints, and analyze the strategies implemented by Bank Syariah Indonesia in managing problematic financing. This study employs a quantitative descriptive approach using secondary data obtained from Bank Syariah Indonesia’s annual reports and financial statements for the period 2021–2025. Data collection was conducted through documentation and literature review. Data analysis involved calculating the Gross NPF and Net NPF ratios and describing their trends over the study period. The results indicate that Bank Syariah Indonesia has been able to maintain its non-performing financing at a healthy level. The Gross NPF ratio decreased from 2.93% in 2021 to 1.81% in 2025, while the Net NPF ratio decreased from 0.87% to 0.47% over the same period.. All NPF ratios during the study period were below the 5% maximum limit set by the Financial Services Authority and were therefore classified as healthy. The decline in the NPF ratio indicates that Bank Syariah Indonesia has effectively implemented financing risk management and has been able to maintain good financing quality during the 2021–2025 period.